KEDUDUKAN HUKUM ATAS HARTA YANG DIHIBAHKAN PADA PERKAWINAN YANG BELUM DICATATKAN TANPA PERSETUJUAN ISTRI (Studi Putusan Pengadilan Negeri Nomor 425/PDT.G/2012/PN.Mdn tanggal 05 November 2012) - MARIA SIANTURI (PREMISE LAW JURNAL, 2016)
A marriage in Indonesia is regulated in Law No. 1/1974 on Marriage. Article 2, paragraph 1 of Marriage Law states that a marriage is legitimate when it is performed according to each religion and belief; paragraph 2 states that each marriage is to be registered according to the prevailing regulations. Based on this Article, the legitimacy of a marriage is interpreted differently in the verdict of the District Court No. 425/Pdt.G/2012/PN.Mdn on November 5, 2012 which states that a marriage is legitimate when it is performed according to religion and belief while registration is only administrative action. The research used descriptive analytic and judicial normative method. The marriage registration can prove that there is a marriage which is recognized by State. An unregistered marriage does not cause legal consequence for husband and wife, children and joint property. Joint property which is registered is considered as dowry brought to a marriage by either side. Hibah (grant) given by a husband on unregistered joint property does not need his wife’s approval. Therefore, active role in registering a marriage is needed to get legal certainty on a wife’s right and property. Keywords : Marriage Legitimacy, Marriage Registration, Legal Consequence of Unregistered Marriage